2012
DOI: 10.1002/cctc.201200092
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of P 450 BM 3 into a p‐Xylene Hydroxylase

Abstract: Reduce, reuse, reengineer! 2,5‐Dimethylphenol is of high interest for the production of temperature stable polymers (>500 K) and as a building block for “next‐generation” plastics. The presented reengineered P 450 BM 3 variant (R 47 S/Y 51 W/I 401 M) has a good catalytic activity (kcat=1950 min−1), excellent coupling efficiency (66 %), and selectivity (>98 %) for 2,5‐dimethylphenol production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…This observation is consistent with previous studies reporting aromatic hydroxylation of substrates like mono-substituted benzenes and o-xylene by P450 BM3 variants containing phenylalanine at position 87. 32,34 Interestingly, no benzylic hydroxylation was observed for 3.…”
Section: Application To Other Structurally Related Nsaids Mefenamic Amentioning
confidence: 90%
“…This observation is consistent with previous studies reporting aromatic hydroxylation of substrates like mono-substituted benzenes and o-xylene by P450 BM3 variants containing phenylalanine at position 87. 32,34 Interestingly, no benzylic hydroxylation was observed for 3.…”
Section: Application To Other Structurally Related Nsaids Mefenamic Amentioning
confidence: 90%
“…However, this biocatalytic system was not able to oxidize o-alkylphenols. Interestingly, recent work has demonstrated that P450 BM3 can be engineered to hydroxylate alkylbenzenes to corresponding alkylphenols (42,43). Should these biocatalysts be coupled to the current alkylphenol oxidation system, an extended biochemical route from alkylbenzenes to oxidized alkylphenols could be created.…”
Section: Discussionmentioning
confidence: 99%
“…Focused mutagenesis is mainly used in semi-rational protein design experiments [14] to improve localized properties such as activity [9,[19][20][21], selectivity [22][23][24] and, less-frequently, thermal resistance [15,25,26]. The prerequisite is a crystal structure or a homology model to identify the 'beneficial' residues that are subsequently randomized [27].…”
Section: State Of the Art And Challengesmentioning
confidence: 99%